Effect of Positivism in Clinical Legal Education (Pandecta Research Law Journal, 2017)
Saat ini, seiring dengan kompleksnya masalah masyarakat, karakter utama hukum modern adalah bersifat rasional. Rasionalitas dicirikan oleh sifat peraturan prosedural hukum. Prosedur, sehingga menjadi dasar hukum yang penting untuk menetapkan apa yang disebut keadilan, bahkan prosedur menjadi lebih penting daripada membicarakan keadilan itu sendiri. Pendidikan hukum, lebih cenderung menghasilkan praktisi profesional. Praktisi hukum yang dihasilkan adalah pelaku hukum yang diharapkan membuat keputusan yang salah dan mana yang benar berdasarkan ketentuan undang-undang. Tulisan ini membahas tentang hubungan metode Clinical Legal Education (CLE) dengan Alumni pendidikan hukum yang tidak hanya mengutamakan kepatuhan kepada hukum positif, namun juga tetap berpedoman pada etika dan upaya mencapai keadilan. Metode yang digunakan untuk penulisan makalah ini adalah penelitian sosio-legal dengan analisis induktif.At present, along with the complexity of the problems of people and society, the main character of modern law is a rational nature. Rationality is characterized by the nature of a procedural rule of law. Procedure, thereby becoming an important legal basis to establish what is called justice, even the procedure becomes more important than talking about justice itself. Legal education, thus more likely to produce professional practitioners. The resulting legal practitioners are legal actors who are expected to make a decision which side is wrong and what is right under the provisions of the law. This paper discusses on the relationship of CLE method to the result of the Law degree who is not only give priority to the compliance procedure as positive law, but also still guided ethics and efforts to achieve justice. The method used for writing this paper is the socio legal research with inductive analysis. Thus, the fact that occurred in the law enforcement practices will be a major premise and provide input and analysis in this paper.